1996
DOI: 10.1063/1.362956
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate-boron concentration on the residual end-of-range defects in 450 °C annealed As+-implanted junctions

Abstract: Evolution of the crystallographic position of As impurities in heavily doped Si crystals as their electrical activity changes Appl.In order to clarify the origin of enhanced leakage currents observed in As ϩ -implanted junctions annealed at a temperature as low as 450°C ͓M. M. Oka, A. Nakada, K. Tomita, T. Shibata, T. Ohmi, and T. Nitta, Jpn. J. Appl. Phys. 34, 796 ͑1995͔͒, two-step implantation/anneal experiments have been conducted and the spatial distribution of end-of-range defects has been investigated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The principle of source-drain activation by low temperature annealing is a solid phase epitaxial regrowth (SPER) of the amorphous layer fabricated by the ion implantation. [5][6][7][8][9][10] Furthermore, the improvement of metal-oxide-semiconductor field-emission transistors (MOSFETs) current drivability without shrinking is also important in order to improve LSI performance. It has been shown that the current drivability of MOSFET is vastly improved by making the device on Si(110) surface.…”
Section: Introductionmentioning
confidence: 99%
“…The principle of source-drain activation by low temperature annealing is a solid phase epitaxial regrowth (SPER) of the amorphous layer fabricated by the ion implantation. [5][6][7][8][9][10] Furthermore, the improvement of metal-oxide-semiconductor field-emission transistors (MOSFETs) current drivability without shrinking is also important in order to improve LSI performance. It has been shown that the current drivability of MOSFET is vastly improved by making the device on Si(110) surface.…”
Section: Introductionmentioning
confidence: 99%